Dissolved Neodymium data in the rainwater in the coastal East China Sea - Hong Che; Zhang Jing; Liu Qian; He Huijun; Zhao Zhi-Qi (PANGAEA, 2021)
Samples were filtered through a 0.40-μm Whatman membrane. The samples were then acidified to a pH of ~2 with high-purity HCl . From each sample, 15-20 L was placed in acid-cleaned bottles for Nd isotope composition analysis, and 500 mL was collected to determine the REE concentration. The filter membranes were cryopreserved for the determination of SPM. REE concentrations and Nd isotope compositions determined in these filtered waters were treated as dissolved-phase measurements (Nd<0.45μm). An unfiltered water sample was directly acidified to a pH <2 with hydrochloric acid after sample collection and then filtered through a 0.40-μm Whatman membrane in a cleanroom to determine the acid-soluble REEs (Nd>0.45μm).